One Health Approaches to Trace Mycobacterium leprae’s Zoonotic Potential Through Time - Urban, Christian; Blom, Alette A.; Pfrengle, Saskia; Walker-Meikle, Kathleen; Stone, Anne C.; Inskip, Sarah A.; Schuenemann, Verena J. (Frontiers in Microbiology, 2021)
Hansen’s Disease (leprosy), mainly caused by infection with Mycobacterium leprae, has accompanied humanity for thousands of years. Although currently rare in Europe, there are over 200,000 new infections annually in South East Asia, Africa and South America. Over the years many disciplines - paleopathology, ancient DNA and other ancient biomolecules, and history - have contributed to a better understanding of leprosy’s past, in particular its history in medieval Europe. We discuss their contributions and potential, especially in relation to the role of inter-species transmission, an unexplored phenomenon in the disease's history. Here, we explore the potential of interdisciplinary approaches that understand disease as a biosocial phenomenon, which is a product of both infection with M. leprae and social behaviours that facilitate transmission and spread. Genetic evidence of M. leprae isolated from archaeological remains combined with systematic zooarchaeological and historical analysis would not only identify when and in what direction transmission occurred, but also key social behaviours and motivations that brought species together. In our opinion, this combination is crucial to understand the disease’s zoonotic past and current potential.